2006
DOI: 10.1074/jbc.m512406200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Chaperone Function and Cochaperone Interaction by Novobiocin in the C-terminal Domain of Hsp90

Abstract: The C-terminal domain of Hsp90 displays independent chaperone activity, mediates dimerization, and contains the MEEVD motif essential for interaction with tetratricopeptide repeat-containing immunophilin cochaperones assembled in mature steroid receptor complexes. An ␣-helical region, upstream of the MEEVD peptide, helps form the dimerization interface and includes a hydrophobic microdomain that contributes to the Hsp90 interaction with the immunophilin cochaperones and corresponds to the binding site for novo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
142
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(151 citation statements)
references
References 68 publications
9
142
0
Order By: Relevance
“…For a mechanistic comparison with NB, the effect of GA on import was also studied. Both drugs have been demonstrated to impair Hsp90 function, although much lower concentrations of GA are typically required: 0.5-10 M GA in live cells or 10 -100 M GA in vitro (48,(53)(54)(55)(56)(57)(58)(59)(60)(61). Such concentrations agree with the ϳ2 M affinity of GA for Hsp90 measured in vitro (53).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…For a mechanistic comparison with NB, the effect of GA on import was also studied. Both drugs have been demonstrated to impair Hsp90 function, although much lower concentrations of GA are typically required: 0.5-10 M GA in live cells or 10 -100 M GA in vitro (48,(53)(54)(55)(56)(57)(58)(59)(60)(61). Such concentrations agree with the ϳ2 M affinity of GA for Hsp90 measured in vitro (53).…”
Section: Resultssupporting
confidence: 72%
“…NB was first reported not to disrupt interactions between Hsp90 and the TPR domain co-chaperones FKBP52 (FK506-binding protein of 52 kDa) and protein phosphatase-5 (15). However, a recent report suggested that, under certain conditions, differential displacement of FKBP52 is observed (61). To investigate whether this is the case for Tom70, the direct interaction between Tom70 and Hsp90 was examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NB targets the C-terminal portion of the protein (23), which is critical for the formation of HSP90 dimers to exert its chaperone activity (24), whereas Rad and GA bind the N-terminal ATPbinding pocket to block the ATP-dependent chaperone cycling (25). On the basis of this information, we generated conditional HSP90α-null mice by floxing exons 9 and 10, which encode the C-terminal region of the protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Novobiocin is a small molecule inhibitor that binds to the CTD of Hsp90 (Marcu et al, 2000a;Marcu et al, 2000b;Soti et al, 2002). Like GA and radicicol, novobiocin inhibits the formation of Hsp90 complexes with client or p23, but unlike GA it also reduces the affinity of Hsp90 for TPR-containing co-chaperones that bind to the CTD (Allan et al, 2006;Yun et al, 2004). The disruption of these Hsp90 complexes suggests that novobiocin causes structural rearrangements within Hsp90 that are distinct from the changes seen with GA. Epigallocatechin gallate (ECGG) the active ingredient found in green tea also directly binds to Hsp90 and acts as an AhR antagonist.…”
Section: Small Molecules Also Shift the Conformation Of Hsp90mentioning
confidence: 99%